Comparison of the IOLMaster 700 and the Pentacam in the Analysis of the Lens Nuclear Density Before the Cataract Surgery - Li, Bowen; Liu, Yuqi; Hu, Yiping; Shi, Mingyu (Frontiers in Medicine, 2021)
Purpose: To evaluate the difference of the lens nuclear density measured before and after mydriasis by using the IOLMaster 700 (Carl Zeiss Meditec AG, Jena, Germany) and the Pentacam Scheimpflug imaging (Pentacam HR, Oculus Incorporation, Wetzlar, Germany) and investigate the relationship between the measurement data and the phacoemulsification parameters. Methods: Patients with age-related nuclear cataracts diagnosed on the slit-lamp examination were enrolled in the age range of 53–76 years. No patient had a history of ocular surgery, laser treatment, or general disorders affecting vision. The mean optical density (OD) was measured by the IOLMaster 700 by using the Image-Pro® Plus software before and after mydriasis. The Pentacam nucleus densitometry (PND) was obtained automatically from the Pentacam Scheimpflug imaging and compared with OD. The correlation between OD and effective phacoemulsification time (EPT), PND, and EPT were analyzed, respectively. Results: In this study, 53 eyes of 52 patients were evaluated. Before and after mydriasis, the mean OD values were 64.34 ± 23.31 and 63.81 ± 23.21 pixel units, respectively; the mean PND values were 28.51 ± 11.42 and 25.41 ± 11.31, respectively; and the mean EPT value was 6.24 ± 3.49. The Bland–Altman analysis showed that the lens nuclear densities of the two devices were highly consistent. There was no significant difference in the OD values (t = 0.455, p > 0.05) before and after mydriasis, but the difference has existed in the PND values (t = 2.509, p < 0.05). The OD and PND values were positively correlated with EPT before and after mydriasis (rOD−Before = 0.604, rOD−After = 0.593, rPND−Before = 0.701, and rPND−After = 0.891, p < 0.01). Conclusion: The combination of the IOLMaster 700 and the Image-Pro® Plus software can quantitatively evaluate the degree of the cataract lens opacification. It has good consistency with the Pentacam and is positively correlated with the phacoemulsification parameters. It is expected to become a new method to predict the phacoemulsification parameters before and during cataract surgery.